Factors Influencing Telehealth Adoption in Managing Healthcare in Saudi Arabia: A Systematic Review - Alamri HM; Alshagrawi S (Journal of Multidisciplinary Healthcare)
Hamad Mohammed Alamri,1 Salah Alshagrawi2 1Ministry of Health, Eastern Health Cluster, Ras Tanura General Hospital, Ras Tanura, Saudi Arabia; 2Department of Public Health, College of Health Sciences, Saudi Electronic University, Riyadh, Saudi ArabiaCorrespondence: Salah Alshagrawi, Email sshagrawi@gmail.comBackground: The utilization of telehealth as an effective means to provide quality services is steadily rising across different tiers of the health system. However, advancing telehealth utilization relies on the current healthcare systems’ infrastructure, policies, cultural factors, and utilization requirements can influence the utilization of telehealth within Saudi Arabia’s healthcare system.Purpose: This study seeks to systematically review the literature related to examining the factors influencing telehealth adoption and identifying the barriers and determinants of the use of telehealth in Saudi’s healthcare system.Methods: A systematic review methodology was utilized in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The methodology included an exploratory and narrative design, a dual-phase search strategy, eligibility criteria, and analysis. The Joanna Briggs Institute (JBI) tool was employed to assess the quality of the chosen papers.Results: The search yielded 3197 articles to which eligibility criteria were applied. Thirteen articles were deemed eligible, screened, and utilized for comprehensive analysis in the present study. Numerous articles indicated that the utilization of telehealth has risen in Saudi Arabia, particularly during the COVID-19 pandemic. The investment strategies have aligned with the demand for telehealth systems. The primary challenges were resource limitations and the absence of cultural frameworks conducive to the utilization of telehealth in the country.Conclusion: Telehealth represents a major technological breakthrough in the healthcare industry. However, there are some drawbacks to its adoption. The limited availability of Telehealth technologies poses a significant challenge. Secondly, relying solely on privatization might not adequately address the issue at hand. Third, there is a lack of knowledge and awareness regarding its associated benefits among healthcare staff. The establishment of telemedicine and telehealth infrastructure necessitates significant financial investment, which serves as a major factor and obstacle to the widespread adoption of telehealth.Keywords: telemedicine, telecare, health services, clinics, healthcare workers, quality management